Indonesian Public Diplomacy in the Covid-19 Pandemic - Lola Dwi Pahlevi Seroja (International Journal Labs, 2023)
The Covid-19 pandemic that has hit the world since the outbreak of the coronavirus that started in the city of Wuhan, China at the end of 2019 has ushered in a new chapter in public diplomacy as many countries around the world implement policies on closing borders, lockdowns and physical distancing. Data collection and analysis are carried out by searching literature studies and observations. Public diplomacy is a process of communication between the government and the foreign public in an effort to realize an understanding of the ideas, values, norms, culture, to the goals and national policies of the country. The COVID-19 pandemic has ushered in a new chapter in public diplomacy as many countries around the world have implemented policies on closing borders, lockdowns and physical distancing.